2005
DOI: 10.1021/jf048545q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Isoflavone Daidzein in Puerariae radix with Micelle-Mediated Extraction and Preconcentration

Abstract: Nonionic surfactant oligo(ethylene glycol) monoalkyl ether (Genapol X-080) was employed as an alternative and effective solvent for the extraction of daidzein from Puerariae radix for the first time. Optimum experimental conditions were established. With 5% Genapol X-080 (w/v), liquid/solid ratio of 25:1 (mL/g), and ultrasonic-assisted extraction for 45 min, the extraction percentage of daidzein reached the highest value. For the preconcentration of daidzein by cloud-point extraction (CPE), sodium chloride was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Daidzin (DZ) is a major isoflavone glycoside from Puerariae radix, a herb widely used in Chinese medicinal formulae for the treatment of diabetes [7][8][9]. Many pharmacological studies have been made on DZ but its effect on blood glucose remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daidzin (DZ) is a major isoflavone glycoside from Puerariae radix, a herb widely used in Chinese medicinal formulae for the treatment of diabetes [7][8][9]. Many pharmacological studies have been made on DZ but its effect on blood glucose remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting glucose uptake by muscles is another effective way to decrease blood glucose [8], in which GLUT4 plays a key role. Glucose uptake assay in C2C12 myotubes showed that DZ significantly promoted glucose consumption by myotubes and enhanced GLUT4 membrane translocation as well, indicating that stimulating glucose uptake by muscles and enhancing GLUT4 membrane translocation may involve in the blood glucose-lowering action of DZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puerarin, daidzin, and daidzein are the major isoflavonoids in its crude extract (Chen et al 2001;Prasain et al 2003Prasain et al , 2007. Several reports have focused on extraction and pharmacological actions of P. radix (He et al 2005;Guo et al 2001). But the antioxidant activity and its antioxidant component(s) have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the daidzein (Fig. 1), as a major isoflavone, was shown as an antigiardial activity, antioxidant action, and potential antidiabetic properties [5]. Recently kudzu roots have been prepared in the form of healthy drinks and dietary supplements that are consumed by the public, it is critical to determine their isoflavone content and concentration [6].…”
Section: Introductionmentioning
confidence: 99%